2022
DOI: 10.2217/fvl-2021-0056
|View full text |Cite
|
Sign up to set email alerts
|

Variation Analysis of SARS-CoV-2 Complete Sequences from Iran

Abstract: Aim: SARS-CoV-2 is an emerging coronavirus that was discovered in China and rapidly spread throughout the world. The authors looked at nucleotide and amino acid variations in SARS-CoV-2 genomes, as well as phylogenetic and evolutionary events in viral genomes, in Iran. Materials & methods: All SARS-CoV-2 sequences that were publicly released between the start of the pandemic and 15 October 2021 were included. Results: The majority of mutations were found in vaccine target proteins, Spike and Nucleocapsid p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…A previous study has shown that this mutation appeared in Iran in May 2020. 50 Of the eight Iranian isolates studied, all have more than one RBD mutation, and the interaction of these mutations could affect binding to the ACE2 receptor. According to the docking results, the effect of the RBD mutations was not consistent with previous studies in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that this mutation appeared in Iran in May 2020. 50 Of the eight Iranian isolates studied, all have more than one RBD mutation, and the interaction of these mutations could affect binding to the ACE2 receptor. According to the docking results, the effect of the RBD mutations was not consistent with previous studies in some cases.…”
Section: Discussionmentioning
confidence: 99%